Court procedures in criminal and civil law [ - Blackmur, Amy; Boland, Michael , 1964-; Martin, Suzanne; Rogers, Christine (Video Education Australasia, 2007)
This engaging and informative program discusses the differences between criminal and civil procedures, focussing on the role of the Magistrates Court in dealing with summary and indictable offences, and the trial procedures in exposing all evidence to reach an out-of-court settlement, how civil disputes are resolved and how this differs from a criminal trial